2022
DOI: 10.1101/2022.03.11.22272061
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

PTPRG activates m6A methyltransferase VIRMA to block mitochondrial autophagy mediated neuronal death in Alzheimer’s disease

Abstract: In Alzheimer's disease (AD), neuronal death is one of the key pathology. However, the initiation of neuronal death in AD is far from clear, and new targets are urgently needed to develop effective therapeutic methods. This study analyzed sequencing data from single-cell RNAseq and spatialomics, and revealed the impact of global single-cell mapping and cell spatial distribution relationships in early stage of AD. We found that microglia subpopulation Mic_PTPRG can anchor neurons based on ligand-receptor interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Meanwhile, we detected an increased expression of genes related to programmed cell death (e.g., FLCN and RASSF2 ) (Cooper et al, 2009; Schmidt and Linehan, 2018), indicating an elevated stress level in oligodendrocytes from both regions. Other examples include the microglia-specific upregulation of PTPRG , a receptor protein tyrosine phosphatase that plays a key role in mediating AD-associated neuronal death (Luo et al, 2022). In astrocytes, we observed a decreased expression of several transmembrane transporters (e.g., AQP4 and SLCO1C1 ) as well as neural transmitter metabolism enzymes (e.g., GLUD1 ), suggesting an impairment of blood-brain barrier (Silva et al, 2021) and altered metabolic state (Kulijewicz-Nawrot et al, 2013) in astrocytes from both regions of the AD brains.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, we detected an increased expression of genes related to programmed cell death (e.g., FLCN and RASSF2 ) (Cooper et al, 2009; Schmidt and Linehan, 2018), indicating an elevated stress level in oligodendrocytes from both regions. Other examples include the microglia-specific upregulation of PTPRG , a receptor protein tyrosine phosphatase that plays a key role in mediating AD-associated neuronal death (Luo et al, 2022). In astrocytes, we observed a decreased expression of several transmembrane transporters (e.g., AQP4 and SLCO1C1 ) as well as neural transmitter metabolism enzymes (e.g., GLUD1 ), suggesting an impairment of blood-brain barrier (Silva et al, 2021) and altered metabolic state (Kulijewicz-Nawrot et al, 2013) in astrocytes from both regions of the AD brains.…”
Section: Introductionmentioning
confidence: 99%
“…Highlighting the role of microglia in the disease, we observed that PTPRG , a protein tyrosine phosphatase receptor, is upregulated in AD and stands out substantially from all other genes in terms of effect size and p-value. PTPRG is an inflammatory marker but its role in the molecular etiology of AD is unclear 43 , 44 . Interestingly, PTPRG is among the three genes (the other two being APOE and DYPD ) that are reliably upregulated in two out of three previous human microglia transcriptome studies 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Many of the LR pairs unique to ARM involved neuroprotective and glioprotective factors, such as APOE-SORL1 [58], CD47-SIRPA [59], and PSAP-GPR37L1 [60]) (Supplementary Figure S10). In contrast, disease-enriched LR pairs involving pathology-associated microglia included mediators of cellular damage, including complement (C3-CD46) [61], cholesterol scavenger receptors (PTDSS1-SCARB1) [62], and drivers of microglia-mediated neuronal death (CNTN4-PTPRG) [63] (Supplementary Figure S11). Other LR pairs were shared by both types of disease-associated microglia such as interactions involving the AD disease gene APOE with LRP5, but these were different from those with homeostatic or dystrophic microglia (Supplementary Figures S12 and S13; Supplementary Tables S8-S10).…”
Section: Multinichenet Reveals Markedly Increased CCI Involving Deple...mentioning
confidence: 99%